(1475) INP database management system نظام إدارة قاعدة بيانات INP - El-daoushy, Abdalla (The Institute of National Planning, 2018)
INFORMATION in industry , commerce , planning , . . . , etc can be as vital as finance . Development may depend on efficiency of management of information , and efficiency , in turn , may depend on computerization . . The early use of computers in organizations tend to concentrate on clerical functions such as payroll accounting and processing of customer accounts. Now, they emphasize on applications which provide information processing support for managerial functions. Q system built arround this emphasis is often termed a " Management Information System or M18 “.